PRINCIPLES OF IMPROVING THE CHARACTERISTICS OF TELEMETRY CHANNELS OF UNMANNED AIRCRAFT - BOYKO, SERHIY; STUSCHANSKIY, YURIY; DERYABINA, INNA; PANCHENKO, VIKTOR; HRYBANOVA, SVITLANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to the issues of improving the characteristics of radio communication channels and telemetry of unmanned aerial vehicles. It has been determined that the communication range depends not only on the modem, but also on the antennas, antenna cables, radio wave propagation conditions, external interference, and other reasons.The communication range is determined by such antenna parameters as the transmitter antenna gain and the receiver gain. The article defines the basic principles for improving the characteristics of radio communication channels and telemetry of unmanned aerial vehicles under various meteorological operating conditions, the effects of electromagnetic interference and terrain relief. It has been determined that to obtain the maximum possible communication range, it is necessary to use cables with the minimum possible attenuation and minimize the length of these cables. In the UAV body, the modem should be located as close as possible to the antenna. The degree of influence of the Earth's surface on the connection also depends on the height of the antennas. The higher the height of the antennas, the greater the distance that can be separated from the points without allowing objects or the underlying surface to fall into the significant zone. It is proposed to take into account the location of antennas, both on the ground and on board the UAV, so that during UAV maneuvers, at least for one of the UAV antennas on the NS - UAV antenna line there are no elements of the UAV design. Thus, it is determined that the loss of communication with the UAV of a certain range can be caused by a local decrease in field strength due to oscillations, thus, if you fly some more distance, the connection can be restored. The final loss of communication will occur only after a significant area is completely covered by objects on the ground or surface relief.
Keywords: unmanned aerial vehicles; radio telemetry channels; radio communication range; electronic warfare means; he critical zone of radio wave propagation